2016
DOI: 10.1177/1933719115625849
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression is Altered in Granulosa Cells of Ovarian Hyperresponders

Abstract: Controlled ovarian stimulation plays an integral role in assisted reproduction technology, but individual patients have different responses to exogenous gonadotropins. In order to determine whether microRNAs (miRNAs) have a regulatory role in ovarian response, we profiled the expression of microRNAs in isolated ovarian granulosa cells collected from ovarian hyperresponders and normal responders using microarrays and validated the expression of selected miRNAs using quantitative polymerase chain reaction (PCR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In our previous study [2], bioinformatics analysis of miRNAs with altered expression in ovarian hyperresponders revealed that the target genes of differential miRNAs were enriched in pathways such as cell-cycle regulation. In this study, we found that increased hsa-miR-423-5p can cause a large number of KGN cells to arrest in the G0/G1 phase, with the number of cells in S phase increased when hsa-miR-423-5p expression was inhibited.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous study [2], bioinformatics analysis of miRNAs with altered expression in ovarian hyperresponders revealed that the target genes of differential miRNAs were enriched in pathways such as cell-cycle regulation. In this study, we found that increased hsa-miR-423-5p can cause a large number of KGN cells to arrest in the G0/G1 phase, with the number of cells in S phase increased when hsa-miR-423-5p expression was inhibited.…”
Section: Discussionmentioning
confidence: 96%
“…However, due to the different sensitivities of patients to ovulation-promoting drugs, ovarian response significantly varies among different individuals, and even within the same individual between different cycles [1]. In our previous study [2], we found that miR-423-5p expression in the granulosa cells of patients with high ovarian response to exogenous gonadotropins (the patients who had over 14 oocytes retrieved in IVF treatment, hereinafter referred to as "ovarian hyperresponders") decreased significantly, suggesting that it may play an important role in the regulation of ovarian response. Indeed, MiR-423-5p may alter the expression level of its target genes to cause changes in the number and function of granulosa cells and may increase the sensitivity of ovarian hyperresponders to ovulationinducing drugs.…”
Section: Introductionmentioning
confidence: 91%
“…Yi et al (2006) have shown that miR-200 and miR-19/20 were members of two miRNA families expressed in the skin tissue of embryonic mice and that miR-202 can be used as a useful biomarker of skin tissue function. Other studies indicate a physiological association between increases in follicular miRNA levels and hormone secretion levels in mammals, which involved signaling pathways involved in follicular cell proliferation, steroidogenesis, prevention of premature luteinization, and oocyte maturation (Sontakke et al, 2014;Donadeu et al, 2016;Xie et al, 2016). miR-202 inhibits tumor progression and (Farhana et al, 2015;Lin et al, 2016;Meng et al, 2016) affects the immune system (Fornari et al, 2015;Owen et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…All quantitative data are presented as means ± standard error of the mean, with at least three biological replicates used per analysis. Two-tailed Student's t-test was utilized to analyze the significance of difference between two groups, whereas categorical data were analyzed using the χ 2 or Fisher exact tests. P < 0.05 was considered to indicate a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the different sensitivities of patients to ovulation-promoting drugs, ovarian response significantly varies among different individuals, and even within the same individual between different cycles [1]. In our previous study [2], we found that miR-423-5p expression in the granulosa cells of patients with high ovarian response to exogenous gonadotropins (the patients who had over 14 oocytes retrieved in IVF treatment, hereinafter referred to as "ovarian hyperresponders") decreased significantly, suggesting that it may play an important role in the regulation of ovarian response. Indeed, MiR-423-5p may alter the expression level of its target genes to cause changes in the number and function of granulosa cells and may increase the sensitivity of ovarian hyperresponders to ovulation-inducing drugs.…”
Section: Introductionmentioning
confidence: 91%